Feasibility and Enjoyment of Exercise Video Games in Older Adults - Freed, Sara A.; Sprague, Briana N.; Stephan, Abigail T.; Doyle, Cassidy E.; Tian, Junyan; Phillips, Christine B.; Ross, Lesley A. (Frontiers in Public Health, 2021)
Introduction: Several interventions have been developed to enhance social connectedness among older adults. However, little research has demonstrated their performance in a social distancing environment. Exergames are not only beneficial to older adults' physical and cognitive health, but they also allow players to interact with each other at a distance, which can reduce loneliness and increase social connection. The aim of this pilot study was to investigate older adults' perceptions of two commercially available exergames. Methods: Twenty healthy community-dwelling older adults (M age = 73.30, SD = 5.95, range = 65–84 years, 80% women) were recruited in this pilot study between July 2019 and February 2020. They were asked to play two exergames for 10 min each on the Xbox One with Kinect console: Just Dance and Kinect Sports Rivals. After gameplay, they provided both quantitative and qualitative feedback on these games. Results: Participants reported an average rating for exergame enjoyment. Greater enjoyment was significantly related with younger age and greater extraversion but not gender. Participants were highly motivated to do well on the games but reported lower scores for likelihood of playing these games in the future. Greater likelihood of future play was associated with younger age but not gender or extraversion. “Not aerobic or strengthen enough; not enough exertion,” and “slower movements, repetition, clear purpose of doing the exercise” were some factors that would influence their decision to buy and play these games. Discussion: The preliminary results of this pilot study suggest that exergames may help address social isolation and loneliness—particularly during times of social distancing. Before applying exergames as a social isolation or loneliness intervention for older adults, study replication in larger representative studies and future work that examines important design issues related to older adults' experiences with these games is needed.